Safety and efficacy of protamine after transcatheter aortic valve replacement - Lakshmi Durga Kumaraguruparan; Asuwin Anandaram; Kamalakkannan G. Sambandam; Yogapriya Chidambaram; Bharath Raj Kidambi; Gautam Ganesan Karthikeyan; Madhesh Kasi; Rizwan Suliankatchi Abdulkader; Sankaran Ramesh; Vadivelu Ramalingam; Ravindran Rajendran; Nagendra Boopathy Senguttuvan (Indian Heart Journal)
Transfemoral Trans-catheter Aortic Valve Replacement (TF-TAVR) is a safe alternative to surgical aortic valve replacement (SAVR). Protamine is used to reverse heparin and reduce post-TAVR bleeding, but concerns about risks like valve thrombosis and stroke remain. This systematic review and meta-analysis, following PRISMA guidelines, found no statistically significant difference in major bleeding complications between the protamine and control groups [(3.0 % vs. 14.4 %); RR: 0.56; P = 0.16]. No differences were noted in life-threatening bleeding, blood transfusions, 30-day mortality, or stroke. Protamine appears safe post-TAVR without increasing stroke risk, but its effectiveness in reducing bleeding needs further investigation through a multicentric randomized study.